2021
DOI: 10.3389/fneur.2021.742654
|View full text |Cite
|
Sign up to set email alerts
|

Remote Evaluation of Parkinson's Disease Using a Conventional Webcam and Artificial Intelligence

Abstract: Objective: This study aimed to prove the concept of a new optical video-based system to measure Parkinson's disease (PD) remotely using an accessible standard webcam.Methods: We consecutively enrolled a cohort of 42 patients with PD and healthy subjects (HSs). The participants were recorded performing MDS-UPDRS III bradykinesia upper limb tasks with a computer webcam. The video frames were processed using the artificial intelligence algorithms tracking the movements of the hands. The video extracted features w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 31 publications
0
30
0
2
Order By: Relevance
“…It has been shown that remote assessment of MDS-UPDRS III is feasible via videoconferencing, except for specific items such as rigidity, or postural instability, which are not as important as bradykinesia for general evaluation of the disease [ 33, 34 ]. Indeed, some studies, which restricted bradykinesia assessment to the upper limb motor tasks of the MDS-UPDRS III, showed that upper limb motor performance was a predictive feature of PD onset and progression [ 21, 35 ]. Research on remote evaluation of PD patients has been mainly focused on the use of technological devices [ 14, 15, 36, 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that remote assessment of MDS-UPDRS III is feasible via videoconferencing, except for specific items such as rigidity, or postural instability, which are not as important as bradykinesia for general evaluation of the disease [ 33, 34 ]. Indeed, some studies, which restricted bradykinesia assessment to the upper limb motor tasks of the MDS-UPDRS III, showed that upper limb motor performance was a predictive feature of PD onset and progression [ 21, 35 ]. Research on remote evaluation of PD patients has been mainly focused on the use of technological devices [ 14, 15, 36, 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although digital tools have been recently developed in an attempt to improve bradykinesia scoring by providing quantitative measures [14][15][16], they exhibit limited use in practice because they rely on wearable sensors on patients [17,18] in a dedicated room or need specific conditions [15,[18][19][20]. More recent studies aimed to circumvent these material issues by developing video-based only tools [12,[21][22][23][24]. First, machine learning-based automatic rating for rest tremor and finger tapping was investigated to measure bradykinesia [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that remote assessment of MDS-UPDRS III is feasible via videoconferencing, except for specific items such as rigidity, or postural instability, which are not as important as bradykinesia for general evaluation of the disease [30,31]. Indeed, some studies, which restricted bradykinesia assessment to the upper limb motor tasks of the MDS-UPDRS III, showed that upper limb motor performance was a predictive feature of PD onset and progression [22,32]. Research on remote evaluation of PD patients has been mainly focused on the use of technological devices [14,15,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Another work assessed the global PD severity applying deep learning approach to automatically score the severity level by compiling 7 of the 18 items of the MDS-UPDRS III [21]. Finally, Monje et al investigated MDS-UPDRS III bradykinesia upper limbs tasks but with the constraint of fixed webcam recordings and with different assessment guidelines from MDS-UPDRS [22]. Although these studies bring interesting approaches, it remains to develop tools to closely establish medically-relevant metrics for a better assessment of bradykinesia.…”
Section: Introductionmentioning
confidence: 99%